Development of a Magnetic LED-based Sterilisator for Inactivation of Contaminant Bacteria - Yonatan .; Suryani Dyah Astuti; Khusnul Ain; Deny Arifianto; Ahmad Khalil Yaqubi; Perwira Annissa Dyah Permatasari (Polytechnic)
Nosocomial infections are caused by viruses, bacteria, and fungi that patients acquire while receiving treatment in a healthcare facility. These infections often result from cross-contamination, either through the hands of healthcare workers or contaminated medical equipment. Staphylococcus aureus is a well-known pathogen responsible for many infections, from mild skin conditions to severe sepsis or multiorgan failure. Sterilization is a process designed to eliminate or destroy all forms of microorganisms, including bacteria, fungi, and viruses, on objects or in environments, preventing them from reproducing or causing infections. Static Magnetic Fields (SMF) and Photodynamic Inactivation (PDI), two more recent technologies, provide alternatives to conventional treatments like autoclaving, which have drawbacks. While SMF damages cellular structures, PDI utilizes blue light to create ROS that harm bacteria. PDI and SMF together improve bacterial inactivation, especially S. aureus. This study aims to evaluate combining a static magnetic field with photodynamic inactivation to the inactivation of S. aureus (a Gram-positive bacterium). The research utilized high-power blue LEDs and static magnetic fields generated by neodymium magnets. The highest reduction in bacterial count, 81.92% ± 7.92%, was observed with the combined treatment of static magnetic fields and LED illumination at the F8 microplate location, with an exposure time of 40 min. The LED energy density was 11.72 J/cm2 , and the static magnetic field strength was 25.61 mT. Conversely, the lowest reduction, 52.41% ± 7.64%, occurred at the exact F8 microplate location with a 10-min exposure, an LED energy density of 2.93 J/cm2 , and a static magnetic field strength of 25.61 mT